A Meta‐analysis for Exploring the Diverse Causes and Effects of Stress in Teachers - Montgomery, Cameron; Rupp, André (Canadian Journal of Education/Revue canadienne de l’éducation, 2005)
This study provides a correlational meta‐analysis of 65 independently written or published studies on teacher stress between 1998 and 2003. We measured the relationships between teacher stress and numerous other constructs including coping, burnout, emotional responses, personality mediators, personal support, environmental structure, and background characteristics. A theoretical‐empirical model of construct relationships investigated across studies was developed and n = 2,527 correlational effect sizes were used to estimate the empirical relationships between the operationalized theoretical constructs. Results showed that the strongest association of teacher stressors exists with negatively oriented emotional responses confirming the central role of teachers’ coping mechanisms, personality mediators, and burnout potential according to our model of the stress cycle. Key words: stress, coping, teacher burn‐out, teacher emotional response Cette recherche fournit une méta‐analyse corrélationnelle de 65 études, rédigées ou publiées entre 1998 et 2003, sur le stress chez les enseignants. Les auteurs ont mesuré les relations entre le stress des enseignants et de nombreux autres construits, dont l’adaptation au stress, l’épuisement professionnel, les réactions émotionnelles, les personality mediators, le soutien personnel, la structure du milieu et les antécédents. Un modèle théorico‐empirique des relations entre les construits a été élaboré et des valeurs d’effets corrélationnels de n = 2527 ont été utilisées pour déterminer les relations empiriques entre les construits théoriques opérationalisés. Les résultats démontrent que, pour les facteurs de stress chez les enseignants, l’association la plus importante se trouve du côté des réactions émotionnelles négatives, ce qui confirme le rôle clé des mécanismes d’adaptation au stress des enseignants, des personality mediators et du potentiel d’épuisement professionnel selon le modèle du cycle du stress qui a été utilisé. Mots clés : stress, adaptation au stress, méta‐analyse, enseignants.